Mediação da leitura para a pessoa idosa na Biblioteca Pública Municipal Mário Cabral - Santana, Veronica Cardoso de (2020)
The mediation of reading developed in libraries enables the interaction between the individual and the book, promotes the cognitive development of the reader. Within this perspective, this work has as a general objective: to carry out reading mediation for the elderly in order to favor the dialogue and interaction between them and the redefinition of the use of the Municipal Public Library Mário Cabral, outlines for this purpose, the following specific objectives : 1) to know the benefits of reading for the elderly participating in mediation activities; 2) identify the type of literature preferred by the elderly in order to favor the process of mediation of reading; 3) verify if there was a greater interaction between the elderly and the Library from the activity performed and the consequent use of its products and services 4) perceive, from the reading mediation, if the elderly showed interest in practicing reading on a daily basis ; 5) consolidate, as a product of the intervention of this research, a video that demonstrates step by step, how to mediate reading for the elderly. In methodological terms, the study in question is configured as participatory research and case study, with a qualitative and applied approach using the descriptive research method. As a result of the research, we achieved the objectives set, as well as, the understanding of the CRAS senior citizens Carlos Hadman Cortês participating in the project, about the importance of the Public Library for the development of human beings in society, as well as the role of the librarian as mediator of information. It is concluded that, reading is important to help in the prevention of diseases of the central nervous system, besides providing the cognitive and social development of the elderly person.